THE ROLE OF PADANG LOCAL GOVERNMENT PUBLIC RELATIONS IN SUCCESS PREVENTION AND ERADICATION OF DENGUE HEMORRHAGIC FEVER - Mardia Nelisna (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2014)
Government Public Relations as a communicator plays an important role in the era of self-reliance. Strategic role of government public relations is needed in achieving good governance. Increase in dengue hemorrhagic fever cases in the city of Padang has reached an alarming circumstance. To prevent and control this case required the cooperation of all parties supported by the active participation of the community. Government Public relations play an important role in helping to prevent and control dengue programs including : health campaigns, coordination with local government working units, media cooperation , building a positive image, and negotiations with the private sector. Only the reality is the role of government public relations in helping the prevention and control of dengue successfull, has not come out, more focus to the work of public relations existing routin . Budget constraints and weak public relations positions make less powerful publicist. Keywords : Government Public Relations , Autonomy , Transparancy , Good Governance , Dengue Hemorrhagic Fever.